Use the product rule whenever there is a function that's a product of two other functions of x. If
f(x) = ({something with an x}) × ({something else with an x}),
then use the product rule to find f'.
To use the product rule, figure out which two functions are multiplied together, and the derivative of each of those functions.
Find the derivative of h(x) = x^{2}e^{x}. |
Find the derivative of f(x) = sin x cos x. |
Find the derivative of g(x) = x^{2}sin x |
Find the derivative of f(x) = 4x^{2}. |
Find the derivative of f(x) = x^{2}e^{x}sin x. |
Let f(x) = x + 1 and g(x) = x.
Let f(x) = x + 1 and g(x) = x.
Let f(x) = x + 1 and g(x) = x.
Let f(x) = x + 1 and g(x) = x.
Let f(x) = x + 1 and g(x) = x.
Find the derivative of each function. They may not all require the product rule.
Find the derivative of each function. They may not all require the product rule.
Find the derivative of each function. They may not all require the product rule.
Find the derivative of each function. They may not all require the product rule.
Find the derivative of each function. They may not all require the product rule.
Find the derivative of each function. They may not all require the product rule.
Find the derivative of each function. They may not all require the product rule.
Find the derivative of each function. They may not all require the product rule.
Find the derivative of each function. They may not all require the product rule.
Find the derivative of each function. They may not all require the product rule.
Find the derivative of f(x) = (x^{2} + 2)(x^{3}-4).
Find the derivative of f(x) = (x^{2} + 2)(x^{3}-4).
f(x) = x^{2}e^{x}sin x
thinking of the function as
f(x) = (x^{2})(e^{x}sin x).
Find the derivative of the function
f(x) = x^{3}sin x cos x
in two different ways. Give the answer with everything multiplied out (instead of factoring out common factors).